Umat Kristiani dan Politik Praktis di Indonesia: Dari Politik Minoritas ke Politik Pluralisme - Sinaga, Martin Lukito (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
Abstract: Theological attitude and political position of Christians in Indonesia is ambivalent, wich cause these people to be cornered as minority parasite. This situation needs to be adressed, and deeper understanding of Reformed heritage and Sam Ratulangis struggle in the dire era of Indonesian birth in 1945 can inspire a new mode of theology and Indonesian Christian political presence today. In this light, the strategic direction of Christian politics lies in the pluralism political movement. KEYWORS: incognito, civil obedience, minority politics, majoritarianism, politics of citizenship plurality